2016
DOI: 10.1038/nrc.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Beyond transcription factors: how oncogenic signalling reshapes the epigenetic landscape

Abstract: Cancer, once thought to be caused largely by genetic alterations, is now considered to be a mixed genetic and epigenetic disease. The epigenetic landscape, which is dictated by covalent DNA and histone modifications, is profoundly altered in transformed cells. These abnormalities may arise due to mutations in or altered expression of chromatin modifiers. Recent reports on the interplay between cellular signaling pathways and chromatin modifications add another layer of complexity to the already complex regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 172 publications
(186 reference statements)
0
68
0
Order By: Relevance
“…The epigenome (the collective sum of all epigenetic information) contains hypervariable regions and is temporally and spatially regulated, such that there are as many epigenomes as there are cell types (23) and cell states (24, 25). DNA methylation is the most extensively characterized epigenetic mechanism (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…The epigenome (the collective sum of all epigenetic information) contains hypervariable regions and is temporally and spatially regulated, such that there are as many epigenomes as there are cell types (23) and cell states (24, 25). DNA methylation is the most extensively characterized epigenetic mechanism (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic stress (e.g., due to overexpression of an oncogene) in human cells induces the expression of a histone H3K27 demethylase JMJD3, which in turn removes repressive H3K27me3 marks on tumor suppressor genes p16 INK4A and p14 ARF to help initiate cellular senescence 34 . To date, over 20 phosphorylation sites on histones regulated by upstream signaling kinases have been reported 2 . Another specific stress response, the DNA damage response (DDR), is intimately linked to chromatin modifications 35 .…”
Section: Strategies For the Epigenetic Inheritance Of Stress Responsementioning
confidence: 99%
“…It has been proposed that, although some epigenetic changes are transient and can be reversed by chromatin modifiers, others may leave a lasting ‘epigenetic memory’ on chromatin, causing cells to be ‘locked’ in specific gene expression states 2 . Despite the appeal of this idea, experimental evidence (especially at the single cell level) in support of this hypothesis is still lacking.…”
Section: Strategies For the Epigenetic Inheritance Of Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, using either exome sequencing [55] or targeted cancer panels [56], two pilot studies identified actionable mutations in 27–31% of children with several cancer diagnoses (n=100–150). Whole genome sequencing has also started to delineate the genetic landscapes across several pediatric cancer subtypes, and to identify rare structural alterations undetectable by targeted panels or whole exome sequencing [57] More interestingly, epigenetic analyses alongside whole genome sequencing of retinoblastoma showed that upregulation of the proto-oncogene SYK is required for tumor survivor, while its inhibition leads to retinoblastoma tumor cell death [58] Additional studies have started to uncover the complex interplay between genomic alterations and the cancer epigenomic landscape, opening new avenues for targeted therapy [59]. Integration of genomic, transcriptomic, and epigenomic data will certainly revolutionize the field of precision medicine, and unravel novel biological pathways with new insights into targeted therapy.…”
Section: Diagnostic Utilitymentioning
confidence: 99%